2008
DOI: 10.1016/j.powtec.2007.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Fluidization of Group B particles with a rotating distributor

Abstract: A novel rotating distributor fluidized bed is presented. The distributor is a rotating perforated plate, with 1% open-area ratio. This work evaluates the performance of this new design, considering pressure drop, Δp, and quality of fluidization. Bed fluidization was easily achieved with the proposed device, improving the solid mixing and the quality of fluidization.In order to examine the effect of the rotational speed of the distributor plate on the hydrodynamic behavior of the bed, minimum fluidization veloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 21 publications
1
20
0
Order By: Relevance
“…The fixed bed height (h b ) was varied throughout the experiments between 0.25D and 0.75D. The minimum fluidization velocity was measured to be 0.31 m/s for the rotating distributor bed and 0.33 m/s for the static one, thus the minimum fluidization velocity slightly decreases with the rotation, in agreement with Sobrino et al [24].…”
Section: Methodssupporting
confidence: 85%
See 2 more Smart Citations
“…The fixed bed height (h b ) was varied throughout the experiments between 0.25D and 0.75D. The minimum fluidization velocity was measured to be 0.31 m/s for the rotating distributor bed and 0.33 m/s for the static one, thus the minimum fluidization velocity slightly decreases with the rotation, in agreement with Sobrino et al [24].…”
Section: Methodssupporting
confidence: 85%
“…Sobrino et al [24], using a similar experimental setup to the one used in the present experiments, showed that a rotating distributor may affect global bed parameters. For instance, they showed that, as a consequence of rotation, bubble diameter is affected, and become more homogeneous along the bed and minimum fluidization velocity decreases.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…3. In addition to the 2D measurements, several measurements were obtained from a 3D bed that was similar to the one described in the literature [31]. These data were used to obtain the minimum fluidization velocity in a 3D bed.…”
Section: Experimental Set-upmentioning
confidence: 99%
“…It has been previously reported that the rotating distributor motion promotes an increase in the radial dispersion of particles, preventing the temperature gradients by reducing high particle concentration zones present within fluidized beds [19,20]. Furthermore, there is some experimental evidence that the stagnant zones just above the distributor could be broken by the rotating distributor, improving the radial and axial mixing at the bottom of the bed [21].…”
Section: Introductionmentioning
confidence: 99%